Estimación del potencial de secuestro de carbono de la especie Prosopis pallida en bosque seco El Algarrobal – Laredo 2022 - Asmad Quintana, José Miguel (2023)
Research on the ecosystem service of carbon sequestration in the dry forests of Peru is limited. The main objective of this research was to estimate the carbon sequestration potential of the vulnerable forest species Prosopis pallida, located in the El Algarrobal dry forest in Laredo, through the methodology of the "World Agroforestry Center" (ICRAF). In the forest inventory, 151 individuals of Prosopis pallida with a diameter at breast height (DBH) greater than 10 cm were measured, systematically located in four plots with an extension of 0,25 ha. The allometric model used to determine aerial biomass was that of Llanos (2010), which consisted of the use of the DAP and height variables. After an ANOVA statistical analysis, it was estimated that carbon sequestration was 36,51 tC in the 3,31 ha of forest cover extension of the forest. Likewise, the average carbon sequestration per individual was 0,057 tC, exceeding four times the value reported by Chávez (2018) in a dry carob forest on the Lambayeque coast, where it was 0,014 tC. This finding suggests that the El Algarrobal dry forest has a high potential for carbon sequestration. In addition, using the "market prices" method, the economic value of the ecosystem service was determined, which was $11378,52, with the European carbon trading system SENDECO2 being the most profitable alternative.